2011
DOI: 10.1063/1.3598404
|View full text |Cite
|
Sign up to set email alerts
|

The transition from a TEM-like mode to a plasmonic mode in parallel-plate waveguides

Abstract: We describe subwavelength-resolved measurements of the broadband terahertz field propagating inside a finite-width parallel-plate waveguide. We observe a transition in the spatial mode of the waveguide, in which the energy distribution shifts from the waveguide center to the edges with increasing frequency. This transition is surprisingly abrupt, and depends sensitively on the gap between the waveguide plates. These results may have important implications for a variety of terahertz experiments as well as in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 21 publications
3
11
1
Order By: Relevance
“…In this situation, these modes interfere destructively at the waveguide center and constructively at the edges, leading to the enhanced electric field near the waveguide edges, similarly to the effect discussed in Ref. 12. In our case, however, this distribution is clearly attributed to the interference of the TEM and TE 02 modes rather than to the formation of plasmon modes .…”
contrasting
confidence: 41%
“…In this situation, these modes interfere destructively at the waveguide center and constructively at the edges, leading to the enhanced electric field near the waveguide edges, similarly to the effect discussed in Ref. 12. In our case, however, this distribution is clearly attributed to the interference of the TEM and TE 02 modes rather than to the formation of plasmon modes .…”
contrasting
confidence: 41%
“…Recently, a method based on scattering of the field from needle tip inserted into the waveguide was demonstrated. 10 In this paper, we present a non-invasive method for characterization of the propagating electric field inside a TPPWG. We adapt the air bias coherent detection (ABCD) technique 11 and apply it to a TPPWG in order to image the THz electric field distribution inside the waveguide along the propagation direction without disturbing the propagation of the guided THz wave.…”
mentioning
confidence: 99%
“…A mature THz technology not only requires THz sources and detectors but also devices to guide and manipulate THz waves. The latter include reflectors [8,9], waveguides [10,11], splitters [12], lenses [13] and modulators [14][15][16]. Modulators could be based on liquid crystals (LCs) as demonstrated by Pan et al [17] who demonstrated for instance switchable phase shifters and filters.…”
mentioning
confidence: 97%